Efficacy of Virtual Technology as the Way Forward for Teaching and Learning with the Experience of a Global Pandemic - Jackson, Emerson Abraham (Educational Challenges, 2021)
The call for institutions and governments across the world to prioritize investments in technology was never treated that seriously as it is now, with the emergence of the COVID-19 pandemic, purportedly claimed to have emerged in China’s Wuhan city. All across the world, institutions are yearning for resources to meet the growing need to support continuity in learning through the new normal of virtual schooling, but the capacity to do so is limited owing to nations’ limited preparedness for such a global scale of health calamity. Technology is certainly the way forward to meet the growing needs of people’s desire to survive, and equally so for employers whose growing competitiveness are much catered for through highly manpower skills workforce. Hence, institutions and governments alike are now seen to be making efforts in adapting to new and emerging technologies in a bid to make it worthwhile to support economic prosperity and livelihoods. The aim is to show growing need in learning through the new normal of virtual schooling, adapting to emerging technologies. Methodology. The analysis of technologies, tools, means like MOODLE, Google-Meet, WebEx Meet, ZOOM. Results. Emerging technologies such as Google-Meet, WebEx Meet, ZOOM and already used platforms like MOODLE need to be hailed given their embedded functionalities to capture variety of ways through which disruptive services can be made to continue. Functionalities embedded in the most commonly used platform like MOODLE and Google-Meet have integrated functionalities to support both virtual classroom and assessment components as opposed to that of WebEx and ZOOM. Conclusion. Emerging technologies should include a synchronized system of Managed Learning Environment (MLE) that makes it possible for assessment materials to be integrated with constructive feedback from teachers.